1997
DOI: 10.1097/00000539-199703000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Morphine Plus Ketamine for Upper Abdominal Surgery

Abstract: Increased postoperative pain may be caused by central nervous system plasticity, which may be related to actions of N-methyl-D-aspartic acid (NMDA) receptors on neurons in the dorsal horn of the spinal cord. Opioids act mainly on presynaptic receptors and reduce neurotransmitter release, while ketamine antagonizes NMDA receptors and prevents wind-up and long-term potentiation. Thus, we postulated that central nervous system sensitization would be prevented more effectively by the preoperative use of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, epidural ketamine as pre-emptive analgesic increased the time between first and second analgesic dose thus prolonging the duration of post-operative analgesia. [ 10 11 ] Number of patients requiring rescue analgesia in Group K was more as compared to Group D but the difference was insignificant. Reduced rescue analgesia requirement resulted in decreased amount of local anaesthetics and other systemic analgesics consumed postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, epidural ketamine as pre-emptive analgesic increased the time between first and second analgesic dose thus prolonging the duration of post-operative analgesia. [ 10 11 ] Number of patients requiring rescue analgesia in Group K was more as compared to Group D but the difference was insignificant. Reduced rescue analgesia requirement resulted in decreased amount of local anaesthetics and other systemic analgesics consumed postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…who used a combination of epidural morphine and ketamine. [ 5 ] Wong et al . also concluded that ketamine potentiates analgesic effect of morphine in postoperative epidural pain control.…”
Section: Discussionmentioning
confidence: 99%
“…in a similar study reported that 56.7% (17 out of 30) patients required supplemental analgesic injections. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations